Nano array for exposing SnO2 high-activity crystal face, preparation method and application of nano array in hydrogen sensing

Pd-SnO2 nanowire arrays were prepared by hydrothermal and reduction methods, which solved the problem of active crystal surface exposure in one-dimensional nanoarrays and realized efficient hydrogen sensor devices that can quickly detect hydrogen at low temperatures.

CN120717819APending Publication Date: 2025-09-30FUJIAN INST OF RES ON THE STRUCTURE OF MATTER CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510786022.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-12
Publication Date
2025-09-30

AI Technical Summary

Technical Problem

Existing technologies make it difficult to achieve a high proportion of exposed active crystal surfaces in one-dimensional nanoarrays, and traditional methods are complex, which increases the difficulty of preparation.

Method used

SnO2 nanoarrays were in situ grown on the substrate by a hydrothermal method, and Pd nanoparticles were loaded using a reduction method to form Pd-SnO2 nanowire arrays. The crystal face exposure ratio was adjusted to achieve highly active crystal face exposure.

Benefits of technology

Under low temperature conditions, the Pd-SnO2 nanowire array detects hydrogen quickly and sensitively with excellent sensitivity and selectivity. The detection limit can reach the ppm level, and it has a fast response speed and good reproducibility.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120717819A_ABST
    Figure CN120717819A_ABST
Patent Text Reader

Abstract

The invention provides a nano array for exposing a SnO2 high-activity crystal face, a preparation method of the nano array and application of the nano array in hydrogen sensing. The preparation method of the Pd-SnO2 nanowire array comprises the following steps: (1) synthesizing a SnO2 nano array on the surface of a substrate; and (2) loading the Pd nano particles on the SnO2 nano array, so as to obtain the Pd-SnO2 nanowire array. The palladium nanoparticle-loaded SnO2 nanowire array can rapidly and sensitively detect hydrogen under a low-temperature condition, has excellent sensitivity, shows excellent selectivity and reliable stability, has a detection lower limit reaching a ppm level, and is high in response speed and good in reproducibility. When the palladium nanoparticle loaded SnO2 nanowire array is used for preparing a hydrogen sensing device, the energy consumption is reduced, and the hydrogen sensing device is safer and more environment-friendly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of sensing technology, and in particular relates to a nanoarray exposing a highly active SnO2 crystal face, a preparation method thereof, and application of the nanoarray in hydrogen sensing. Background Art

[0002] One-dimensional nanomaterials, such as nanowires, nanorods, and nanotubes, have highly uniform orientations and are considered to be ideal electron transport materials. Secondly, the high aspect ratio, high specific surface area, and large number of active sites added by the unsaturated dangling bonds at the interface of 1D materials are all basic characteristics required for gas sensing materials. The nanoarray structure of semiconductor metal oxides (SMOs) not only maintains high thermal and chemical stability, but also has a larger specific surface area and more abundant active sites, which further improves the mass transfer and charge transfer efficiency of the sensing material and is more conducive to the sensing performance of the sensor. At present, there are many methods to prepare SMOs nanoarrays with exposed highly active crystal faces, such as chemical vapor deposition or the use of morphology regulators, capping agents, etc. However, these complex methods and tedious post-processing processes increase the difficulty of synthesis. Therefore, there is an urgent need to find a simple and feasible method to synthesize nanoarrays with highly active surfaces, which is also extremely challenging.

[0003] One-dimensional (1D) nanoarrays (nanowire arrays, nanorod arrays, etc.) on various substrates are considered to be ideal materials for chemical applications. However, achieving the desired morphology of 1D nanoarrays and high exposure of active crystal faces is difficult. This is because traditional surfactant-assisted methods usually change the 1D morphology into other morphologies (such as nanosheets, nanobelts, etc.). In this context, deposition methods (electrodeposition, pulsed laser deposition) have been developed to successfully modulate the crystal faces of 1D arrays and maintain the initial structure. However, this method requires delicate tuning of the complexity of electrochemical parameters and careful control of the surrounding environment, making the preparation work difficult. There is an urgent need to develop a practical method to achieve morphological integrity and high exposure of active crystal faces in 1D nanoarrays. Summary of the Invention

[0004] To solve the above technical problems, the technical solutions provided by this application are as follows:

[0005] A method for preparing a Pd-SnO2 nanowire array, the method comprising:

[0006] (1) Synthesis of SnO2 nanoarrays on the substrate surface;

[0007] (2) Pd nanoparticles are loaded onto SnO2 nanoarrays to obtain Pd-SnO2 nanowire arrays.

[0008] According to an embodiment of the present invention, in step (1), synthesizing the SnO2 nanoarray specifically includes: in-situ growing the seed crystal solution on the substrate through a hydrothermal reaction to obtain a SnO2 nanoarray with a highly active surface exposed.

[0009] According to an embodiment of the present invention, the substrate is selected from substrates known in the art, such as at least one of a ceramic substrate, a sapphire substrate, a mica substrate, a silicon wafer substrate, and the like.

[0010] According to an embodiment of the present invention, the seed solution includes a Sn compound and a solvent.

[0011] Preferably, the Sn compound is selected from at least one of SnCl4·5H2O, Sn(SO4)2, Na2SnO3 and the like.

[0012] Preferably, the solvent is selected from at least one of ethanol, isopropanol, water and the like.

[0013] According to an embodiment of the present invention, the concentration of the Sn compound in the seed crystal solution is 0.001-0.05 mol / L, for example, 0.005 mol / L, 0.01 mol / L, 0.025 mol / L. In the present invention, mol / L can also be represented by M.

[0014] According to an embodiment of the present invention, the conditions of the hydrothermal reaction include: a reaction temperature of 180-280° C., for example, 200° C.; and a reaction time of 1-48 h, for example, 24 h.

[0015] According to an embodiment of the present invention, a seed layer is first grown on the surface of the substrate before the hydrothermal reaction.

[0016] Preferably, the growth of the seed crystal layer specifically includes: coating a seed crystal solution on a substrate and sintering the solution. Further, the sintering temperature is 80-150° C., for example, 100° C., and the sintering time is 1-5 hours, for example, 2 hours.

[0017] According to an embodiment of the present invention, by adjusting the concentration of the seed solution, after the hydrothermal reaction, the exposure ratio of the high active (101) surface of SnO2 to the general active (110) surface in the SnO2 nanoarray grown on the substrate is 0.92-6.02, for example, 1, 2, 3, 4, 5, 6.

[0018] According to an embodiment of the present invention, the SnO2 in the SnO2 nanoarray has a needle-like or rod-like structure.

[0019] According to an embodiment of the present invention, in step (2), metal Pd nanoparticles are loaded on the SnO2 nanoarray by a reduction method to obtain a Pd-SnO2 nanowire array.

[0020] According to an embodiment of the present invention, the reduction method specifically includes: mixing a Pd compound and a ligand under light-shielding conditions, then adding a reducing agent to conduct a reduction reaction to obtain metallic Pd nanoparticles; and loading the metallic Pd nanoparticles onto the SnO2 nanoarray. Preferably, the Pd compound is first dispersed onto the SnO2 nanoarray, and then the reduction reaction is conducted. Exemplarily, the SnO2 nanoarray is immersed in a solution containing the Pd compound and the ligand, and then the reducing agent is added and a reduction reaction is conducted to obtain metallic Pd nanoparticles loaded onto the SnO2 nanoarray.

[0021] Preferably, the Pd compound is selected from at least one of H2PdCl4, PdCl2, Pd(acac)2, etc.

[0022] Preferably, the complexing agent is selected from at least one of sodium citrate, disodium EDTA, and the like.

[0023] Preferably, the reducing agent is selected from at least one of boric acid, ascorbic acid, sodium thiosulfate, glucose, etc. Further, when the reducing agent is selected from boric acid, the reduction method is a sodium borohydride reduction method.

[0024] Preferably, in the reduction method, the concentration of the Pd compound is 0.001-0.01 mol / L, for example, 0.005 mol / L; the concentration of the ligand is 0.01-0.1 mol / L, for example, 0.02 mol / L; and the concentration of the reducing agent is 0.001-0.01 mol / L, for example, 0.0095 mol / L.

[0025] Preferably, in the reduction method, the molar ratio of the Pd compound, the ligand and the reducing agent is 0.001-0.005:0.01:0.03-0.05, for example, 0.002:0.01:0.038, 0.003:0.01:0.038, or 0.004:0.01:0.038.

[0026] Preferably, the reduction method is carried out under stirring conditions.

[0027] Preferably, the reaction temperature of the reduction method is 20-60°C, for example 30°C.

[0028] The present invention also provides a Pd-SnO2 nanowire array, which includes palladium nanoparticles and a SnO2 nanoarray, wherein the palladium nanoparticles are loaded on SnO2.

[0029] According to an embodiment of the present invention, the exposure ratio of the highly active (101) surface of SnO2 to the generally active (110) surface in the SnO2 nanoarray is 0.92-6.02, for example, 1, 2, 3, 4, 5, or 6.

[0030] According to an embodiment of the present invention, the SnO2 in the SnO2 nanoarray has a needle-like or rod-like structure.

[0031] According to an embodiment of the present invention, the palladium nanoparticles are uniformly loaded on SnO2.

[0032] According to an embodiment of the present invention, the Pd-SnO2 nanowire array is obtained by the preparation method according to any one of claims 1-5.

[0033] The present invention also provides application of the Pd-SnO2 nanowire array in gas sensing.

[0034] The present invention also provides a gas sensor, which includes the above-mentioned Pd-SnO2 nanowire array.

[0035] According to an embodiment of the present invention, the gas sensor is sensitive to hydrogen.

[0036] According to an embodiment of the present invention, the theoretical detection limit of the gas sensor for hydrogen is at least 0.47 ppm.

[0037] According to an embodiment of the present invention, the response time of the gas sensor to hydrogen is at least 10 seconds, for example, 20 seconds.

[0038] According to an exemplary embodiment of the present invention, the response value of the gas sensor to 100 ppm of hydrogen at 125° C. is 0.67-135.30.

[0039] The present invention also provides application of the gas sensor in hydrogen detection.

[0040] The beneficial effects of this application are:

[0041] This study utilizes a thermodynamically driven nucleation-aggregation growth mechanism to synthesize SnO2 nanoarrays via a simple hydrothermal method in the absence of surfactants by adjusting the precursor concentration. The resulting arrays reveal highly active SnO2 facets. Furthermore, by adjusting the supersaturation, the exposure ratio of the (110) and (101) facets can be regulated over a wide range. Further investigation of the effect of the facet exposure ratio on gas sensing performance demonstrates that Pd-SnO2 is one of the most ideal hydrogen-sensitive materials currently available.

[0042] Most existing hydrogen-sensitive chemiresistive sensors require test temperatures exceeding 250°C. The present invention's palladium nanoparticle-loaded SnO2 nanowire arrays (e.g., Pd-SnO2-L) can rapidly and sensitively detect hydrogen at low temperatures, exhibiting excellent sensitivity, selectivity, and reliable stability. Their detection limit can reach the ppm level, and they also exhibit fast response speed and good reproducibility. Using the present invention's palladium nanoparticle-loaded SnO2 nanowire arrays to fabricate hydrogen sensors not only reduces energy consumption but also improves safety and environmental friendliness.

[0043] This invention will provide a new perspective and approach for the theory and practice of one-dimensional nanoarray crystal surface regulation, and also provide a new idea for the development of high-performance hydrogen sensors. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 This is a schematic diagram of the process for preparing Pd-SnO2 nanoarrays.

[0045] Figure 2 (a) Response of SnO2 samples with different crystal face exposure ratios (C1 to C7) to 100 ppm hydrogen. (b) Gas sensing performance test of SnO2-H samples with different Pd contents (B1 to B3).

[0046] Figure 3 (a) SEM and (b) TEM images of SnO2 nanoarrays SnO2-L (sample A1) with a seed concentration of 0.005 M. (Insets show the SEM cross-section and selected area electron diffraction pattern, respectively).

[0047] Figure 4 Response-recovery curves of sample C1 (Pd-SnO2-L) in the range of (a) 1-10 ppm and (b) 100-10000 ppm H2.

[0048] Figure 5 These are the response-concentration double-log linear fitting curves of samples C4 and C1, i.e., devices Pd-SnO2-L and Pd-SnO2-H.

[0049] Figure 6 Sample C1 (Pd-SnO2-L) responded to 100 ppm H2 four times with a coefficient of variation (CV) of 21.2%.

[0050] Figure 7 This is the response-recovery normalized curve of sample C1 (Pd-SnO2-L) to 100 ppm H2.

[0051] Figure 8(a) SEM and (b) TEM images of SnO2 nanoarray SnO2-H (sample A4) with a seed crystal concentration of 0.05M; (the insets are the SEM cross-sectional view and the selected area electron diffraction pattern, respectively).

[0052] Figure 9 (a) SEM and (b) TEM images of Pd-SnO2-H (sample C4). (Inset is a high-resolution image of Pd nanoparticles).

[0053] Figure 10 Response-recovery curves of sample C4 (Pd-SnO2-H) in the range of (a) 1-10 ppm and (b) 100-10000 ppm H2.

[0054] Figure 11 Sample C4 (Pd-SnO2-H) responded to 100 ppm H2 four times with a coefficient of variation (CV) of 4.4%.

[0055] Figure 12 This is the response-recovery normalized curve of sample C4 (Pd-SnO2-H) to 100 ppm H2.

[0056] Figure 13 (a) PXRD patterns of SnO2 nanoarrays grown with different seed solution concentrations and (b) I (101) / I (110) Relationship with seed solution concentration.

[0057] Figure 14 SEM images of SnO2 nanoarrays with different seed concentrations; (a) 0.005M, (b) 0.01M, (c) 0.025M, (d) 0.1M, (e) 0.3M and (f) 0.5M (samples A1, A2, A3, A5, A6 and A7; the insets are SEM cross-sectional views, respectively). DETAILED DESCRIPTION

[0058] The technical solutions of the present invention will be described in further detail below with reference to specific embodiments. It should be understood that the following embodiments are merely illustrative and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are encompassed within the scope of protection that the present invention is intended to protect.

[0059] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.

[0060] In the examples, the powder X-ray diffraction (PXRD) of the samples was carried out with a Cu Kα The morphology of the samples was characterized by scanning electron microscope (ZEISS Sigma 500) and transmission electron microscope (JEOL JEM-F200).

[0061] In the embodiment, when the gas-sensitive sensing performance test is performed, the test operating voltage is 5V, the test gas with a concentration gradient is configured in a dynamic gas mixing mode, and the gas flow rate is controlled to be 600sccm.

[0062] The response value is obtained according to the following formula:

[0063] R=(R a –R g ) / R a

[0064] The formula is used for reducing gas detection. If it is used to detect oxidizing gas, the R a , R g Interchange; R a = Sensor resistance in air, R g = Sensor resistance when exposed to target gas.

[0065] All raw materials and chemical reagents used in the production and synthesis of the present invention were purchased from Sinopharm Group, and all reagents and drugs used were used directly without further purification.

[0066] Example 1

[0067] The preparation of Pd-SnO2 nanoarrays is divided into two processes (such as Figure 1 ): The first step is to prepare a SnO2 nanoarray for loading Pd nanoparticles; the second step is to load the Pd nanoparticles on the SnO2 nanoarray using a sodium borohydride reduction method. The specific preparation process is as follows:

[0068] (a) Preparation of SnO2 nanoarrays:

[0069] Using a seed-assisted hydrothermal method, SnCl₄·5H₂O (0.01753 g, seed solution concentration 0.005 M) was first added to 10 mL of ethanol. The solution was then spin-coated onto a cleaned ceramic substrate and sintered in a 100°C oven for 2 hours (heating for 30 minutes and cooling for 30 minutes) to form a SnO₂ seed layer. The ceramic substrate was then placed vertically into a 20 mL reactor liner (with the seed layer facing down). Next, 15 mL of a mixed aqueous solution (0.1 M SnCl₄·5H₂O) and 1 M NaOH) was added to the reactor liner. Finally, the liner was placed in a stainless steel reactor and reacted at 200°C for 24 hours (heating time 6 hours). After the reactor cooled naturally, the ceramic substrate was removed and washed three times with deionized water and anhydrous ethanol, dried with nitrogen, and annealed in a tube furnace at 400°C for 1 hour (air was used as the carrier gas and the heating rate was 5° / min). The resulting array was sample A1, labeled SnO2-L. When the seed solution concentration was 0.005M, the scanning electron microscope (SEM) image showed the morphology of SnO2 nanoneedles ( Figure 3 a), the (110) surface corresponding to SnO2-L can also be clearly observed from the transmission electron microscope (TEM) image ( Figure 3 b).

[0070] (b) Loading of Pd nanoparticles:

[0071] Pd nanoparticles were loaded using the sodium borohydride reduction method. First, the ceramic substrate bearing the SnO2 nanoarray was placed vertically in a 50mL beaker with the front side (i.e., the side bearing the SnO2 nanoarray) facing downward. The height was such that the surface bearing the SnO2 nanoarray could be immersed in the solution in the beaker. Deionized water (38mL) and Na3C6H5O7·2H2O (0.5mL, 0.02M) were then added to the beaker (protected from light by tin foil) and stirred vigorously for 5 minutes. Next, 625μL of H2PdCl4 (5mM) was added, and stirring continued for 10 minutes. Next, 0.4mL of NaBH4 (0.095M) was added, and stirring continued for 30 minutes. The substrate was removed, rinsed several times with deionized water, and dried with N2 gas. The resulting array was designated sample C1 and labeled Pd-SnO2-L.

[0072] (c) Gas sensing performance test

[0073] At 125°C, the dynamic gas-sensitive response of Pd-SnO2-L to H2 at concentrations of 1, 3, 5, 7, 10, 100, 300, 500, 700, 1000 and 10000 ppm was tested. Figure 4As shown. The double log axis curve is linearly fitted, and the correlation coefficient of the fitted straight line is 0.985, which further illustrates that there is a good linear correspondence between the response value and the H2 concentration. According to the fitted straight line of the response ( Figure 5 ), the theoretical detection limit of the device for hydrogen is calculated to be 0.80ppm based on the 10% response value. Figure 6 As shown in Figure 2, the coefficient of variation (CV) of the cyclic response of Pd-SnO2-L to 100ppm hydrogen is 21.2%, indicating that the material has a certain degree of reproducibility. The response value of the Pd-SnO2-L gas sensor device constructed in this embodiment to 100ppm H2 at 125°C is 20.23 ( Figure 2 In (a), the response and recovery times are 20 and 15 seconds respectively ( Figure 7 ).

[0074] Example 2

[0075] The preparation of Pd-SnO2 nanoarrays is divided into two processes (such as Figure 1 ): The first step is to prepare a SnO2 nanoarray for loading Pd nanoparticles; the second step is to load the Pd nanoparticles on the SnO2 nanoarray using a sodium borohydride reduction method. The specific preparation process is as follows:

[0076] (a) Preparation of SnO2 nanoarrays:

[0077] Using the seed-assisted hydrothermal method, first add SnCl4·5H2O (0.1753g, seed solution concentration is 0.05M) to 10mL of ethanol, then spin-coat it on a clean ceramic substrate and sinter it in a 100℃ oven for 2h (heating for 30min and cooling for 30min) to form a SnO2 seed layer. The subsequent steps are the same as in Example 1, and the resulting array is sample A4, labeled SnO2-H. When the seed solution concentration is 0.05M, the SEM photos show that the SnO2 nanorods grow perpendicular to the substrate, and the bottom of the array is densely connected, with bamboo shoot-like protrusions on the top, with a length of about 100-200nm ( Figure 8 From the TEM image, it is clearly observed that the (101) surface of SnO2-H ( Figure 8 (b)

[0078] (b) The loading of Pd nanoparticles is basically the same as in Example 1, except that the SnO2 nanoarray obtained in step (a) of this example is used. The prepared array is sample C4, labeled Pd-SnO2-H.

[0079] Since the particle size of nanoparticles (NPs) is relatively small, after loading Pd NPs, the SEM images ( Figure 9 No Pd was observed in a). Figure 9 As shown in (b), Pd is evenly dispersed on the SnO2 nanoarray, where the lattice spacing of 0.24 nm corresponds to the (111) plane of Pd.

[0080] (c) Gas sensing performance test:

[0081] At 125°C, the dynamic gas-sensitive response of Pd-SnO2-H to H2 at concentrations of 1, 3, 5, 7, 10, 100, 300, 500, 700, 1000 and 10000 ppm was tested. The results are as follows: Figure 10 The double log axis curve was linearly fitted, and the correlation coefficient of the fitted line was 0.996, which further demonstrated that there was a good linear correspondence between the response value and the H2 concentration ( Figure 5 According to the fitting line of the response, the theoretical detection limit of the device for hydrogen is calculated to be 0.47ppm ( Figure 5 ). For example Figure 11 As shown in the figure, the coefficient of variation (CV) of the cyclic response of Pd-SnO2-H to 100ppm hydrogen is only 4.4%, indicating that the material has good reproducibility. The response value of the constructed Pd-SnO2-H gas sensor to 100ppm H2 at 125℃ is 135.30( Figure 2 In (a), the response and recovery times are 20 and 30 seconds respectively ( Figure 12 ).

[0082] Example 3

[0083] The preparation of Pd-SnO2 nanoarrays is divided into two processes (such as Figure 1 ): The first step is to prepare a SnO2 nanoarray for loading Pd nanoparticles; the second step is to load the Pd nanoparticles on the SnO2 nanoarray using a sodium borohydride reduction method. The specific preparation process is as follows:

[0084] (a) Preparation of SnO2 nanoarrays:

[0085] Using a seed-assisted hydrothermal method, different amounts of SnCl₄·5H₂O (0.03506, 0.08767, 0.3506, 1.0518, and 1.753 g, with seed solution concentrations of 0.01, 0.025, 0.1, 0.3, and 0.5 M, respectively) were added to 10 mL of ethanol. The resulting samples were then spin-coated onto a cleaned ceramic substrate and sintered in a 100°C oven for 2 hours (30 minutes of heating and 30 minutes of cooling) to form a SnO₂ seed layer. The subsequent steps were the same as in Example 1, resulting in arrays A2, A3, A5, A6, and A7, respectively.

[0086] like Figure 13As shown in (a), the characteristic peaks of the PXRD of the synthesized material at 26.6° and 33.8° correspond to the (110) and (101) crystal planes, respectively. In addition, when the concentration of the seed solution is 0.005M to 0.05M, the peak intensity ratio (I (101) / I (110) ) increases with the increase of seed solution concentration (A1 to A4). When the seed solution concentration reaches 0.05M, the peak intensity ratio reaches a maximum value of 6.05 ( Figure 13 b). Subsequently, as the concentration of the seed solution further increases, I (101) / I (110) The value gradually decreases. From the SEM plan view, it can be seen that with the increase of the concentration of the seed solution, the density of the nanoarray changes from sparse to dense, and the morphology gradually changes from needle-like to rod-like ( Figure 14 When the concentration exceeds 0.1M, obvious cracks appear on the surface of the SnO2 nanoarray, and the width of the cracks gradually increases with the increase of concentration.

[0087] (b) The loading of Pd nanoparticles was basically the same as in Example 1, except that the SnO2 nanoarray samples A2, A3, A5, A6 and A7 obtained in step (a) of this example were used, and the resulting arrays were recorded as samples C2, C3, C5, C6 and C7, respectively.

[0088] (c) Gas sensing performance test

[0089] At 125°C, the gas-sensitive responses of a series of samples (C2, C3, C5, C6 and C7) to 100 ppm H2 were tested. The results are as follows: Figure 2 As shown in a. As can be seen in the figure, with the increase of the concentration of the precursor solution, the exposure ratio of the crystal plane (101) first increases and then decreases, see Figure 13 (a) PXRD patterns of SnO2 nanoarrays grown with different seed solution concentrations; the response values ​​of the samples to 100ppm hydrogen also showed similar trends, which were 43.27, 72.73, 19.63, 13.90 and 11.74 ( Figure 2 (a)

[0090] Example 4

[0091] The preparation of Pd-SnO2 nanoarrays is divided into two processes (such as Figure 1 ): The first step is to prepare a SnO2 nanoarray for loading Pd nanoparticles; the second step is to load the Pd nanoparticles on the SnO2 nanoarray using a sodium borohydride reduction method. The specific preparation process is as follows:

[0092] (a) Preparation of SnO2 nanoarrays:

[0093] Using a seed-assisted hydrothermal method, SnCl₄·5H₂O (0.1753 g, seed solution concentration 0.05 M) was added to 10 mL of ethanol. The solution was then spin-coated onto a cleaned ceramic substrate and sintered in a 100°C oven for 2 hours (30 minutes of heating and 30 minutes of cooling) to form a SnO₂ seed layer. The subsequent steps were the same as in Example 1. The resulting array was sample A4, labeled SnO₂-H.

[0094] (b) Loading of Pd nanoparticles:

[0095] Pd nanoparticles were loaded using a sodium borohydride reduction method. First, SnO2-H was placed vertically, face down, in a 50 mL beaker. Deionized water (38 mL) and Na3C6H5O7·2H2O (0.5 mL, 0.02 M) were then added to the beaker (protected from light by tin foil) and stirred vigorously for 5 minutes. Next, 325, 500, and 750 μL of H2PdCl4 (5 mM) were added, respectively, and stirring continued for 10 minutes. Next, 0.4 mL of NaBH4 (0.095 M) was added and stirred for 30 minutes. The substrate was removed, rinsed several times with deionized water, and dried with N2 gas. The resulting arrays are samples B1, B2, and B3, labeled Pd-SnO2-L.

[0096] (c) Gas sensing performance test

[0097] At 125°C, the gas-sensitive responses of B1-B3 to 100 ppm H2 were tested. The results are as follows: Figure 2 As shown in Figure 2(b), when the Pd loading was 1.625 and 2.5 μmol, the responses of samples B1 and B2 to 100 ppm hydrogen were 0.67 and 2.67, respectively. However, when the Pd loading was 3.125 μmol (i.e., the sample Pd-SnO2-H), the response to 100 ppm hydrogen reached its maximum value of 135.30. Furthermore, as the Pd loading increased, the response to hydrogen decreased, reaching a value of 17.91 for sample B3. This indicates that the optimal Pd loading for this sensor is 3.125 μmol.

[0098] The above describes exemplary embodiments of the present invention. However, the scope of protection of this application is not limited to the above embodiments. Any modifications, equivalent substitutions, improvements, etc. made by those skilled in the art within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a Pd-SnO2 nanowire array, characterized in that: The preparation method comprises: (1) Synthesis of SnO2 nanoarrays on the substrate surface; (2) Pd nanoparticles are loaded onto SnO2 nanoarrays to obtain Pd-SnO2 nanowire arrays.

2. The preparation method according to claim 1, characterized in that In step (1), the synthesis of SnO2 nanoarrays specifically includes: in situ growing a seed crystal solution on a substrate through a hydrothermal reaction to obtain a SnO2 nanoarray with a highly active surface exposed; And / or, the seed crystal solution comprises a Sn compound and a solvent; and / or, the Sn compound is selected from at least one of SnCl4·5H2O, Sn(SO4)2, and Na2SnO3; And / or, the solvent is selected from at least one of ethanol, isopropanol, and water; And / or, in the seed crystal solution, the concentration of the Sn compound is 0.001-0.05 mol / L.

3. The preparation method according to claim 1 or 2, characterized in that The conditions of the hydrothermal reaction include: reaction temperature of 180-280°C; reaction time of 1-48h; and / or, before the hydrothermal reaction, growing a seed layer on the substrate surface; And / or, the growth of the seed crystal layer specifically includes: coating a seed crystal solution on a substrate and sintering the solution; and / or, by adjusting the concentration of the seed solution, after the hydrothermal reaction, the exposure ratio of the highly active (101) surface of SnO2 to the generally active (110) surface of SnO2 in the SnO2 nanoarray grown on the substrate is 0.92-6.02; And / or, the SnO2 in the SnO2 nanoarray has a needle-like or rod-like structure.

4. The preparation method according to any one of claims 1 to 3, characterized in that In step (2), metal Pd nanoparticles are loaded on SnO2 nanoarrays by a reduction method to obtain Pd-SnO2 nanowire arrays; And / or, the reduction method specifically comprises: mixing a Pd compound and a coordination agent under light-proof conditions, and then adding a reducing agent to carry out a reduction reaction to obtain metallic Pd nanoparticles; Metal Pd nanoparticles are loaded on SnO2 nanoarrays; And / or, the Pd compound is selected from at least one of H2PdCl4, PdCl2, and Pd(acac)2; And / or, the complexing agent is selected from at least one of sodium citrate and disodium EDTA; And / or, the reducing agent is selected from at least one of boric acid, ascorbic acid, sodium thiosulfate, and glucose.

5. The preparation method according to any one of claims 1 to 4, characterized in that In the reduction method, the concentration of the Pd compound is 0.001-0.01 mol / L; the concentration of the complexing agent is 0.01-0.1 mol / L; the concentration of the reducing agent is 0.001-0.01 mol / L; and / or, in the reduction method, the molar ratio of the Pd compound, the ligand, and the reducing agent is 0.001-0.005:0.01:0.03-0.05; and / or, the reduction method is carried out under stirring conditions; And / or, the reaction temperature of the reduction method is 20-60°C.

6. A Pd-SnO2 nanowire array, characterized in that: The Pd-SnO2 nanowire array includes palladium nanoparticles and SnO2 nanoarrays, and the palladium nanoparticles are loaded on SnO2.

7. The Pd-SnO2 nanowire array according to claim 6, characterized in that: The exposure ratio of the highly active (101) surface of SnO2 to the generally active (110) surface in the SnO2 nanoarrays is 0.92-6.02; and / or, the SnO2 in the SnO2 nanoarray has a needle-like or rod-like structure; and / or, the palladium nanoparticles are uniformly loaded on SnO2; And / or, the Pd-SnO2 nanowire array is obtained by the preparation method according to any one of claims 1-5.

8. Use of the Pd-SnO2 nanowire array according to claim 6 or 7 in gas sensing.

9. A gas sensor, characterized in that: The gas sensor comprises the Pd-SnO2 nanowire array according to claim 6 or 7; and / or, the gas sensor is sensitive to hydrogen; and / or, the gas sensor has a theoretical detection limit of at least 0.47 ppm for hydrogen; And / or, the response time of the gas sensor to hydrogen is at least 10 seconds.

10. Use of the gas sensor according to claim 9 in hydrogen detection.